This Book Is an Action : Feminist Print Culture and Activist Aesthetics - Farr, Cecilia Konchar, 1958-; Harker, Jaime (Book collections on Project MUSE., 2016)
"The Women's Liberation Movement held a foundational belief in the written word's power to incite social change. In this new collection, Jaime Harker and Cecilia Konchar Farr curate essays that reveal how second-wave feminists embraced this potential with a vengeance. The authors in This Book Is an Action investigate the dynamic print culture that emerged as the feminist movement reawakened in the late 1960s. The works created by women shined a light on taboo topics and offered inspiring accounts of personal transformation. Yet, as the essayists reveal, the texts represented something far greater: a distinct and influential American literary renaissance. On the one hand, feminists took control of the process by building a network of publishers and distributors owned and operated by women. On the other, women writers threw off convention to venture into radical and experimental forms, poetry, and genre storytelling, and in so doing created works that raised the consciousness of a generation. Examining feminist print culture from its structures and systems to defining texts by Margaret Atwood and Alice Walker, This Book Is an Action suggests untapped possibilities for the critical and aesthetic analysis of the diverse range of literary production during feminism's second wave"--